A Short-Cut Approach on Batch Distillation Column Design - Wenfeng Hao (Progress in Chemical Science Research Vol. 1, 2022)
To solve the complexity problems that the batch distillation column design must be referred to the continuous distillation column design theories in many cases or to overcome the uncertainty shortcomings that the batch distillation column design have to be originated from an empirical method or from a semi-empirical method, a new shortcut design approach is proposed to determine the number of theoretical and actual plates and the height of the batch distillation column in this paper. Effects of equipment parameters of batch distillation column on the yield proportion are discussed and analyzed, relations between maximal yield proportion and column equipment parameters are correlated. Under the assistance of the separation difficulty defined, the minimum number of the theoretical plates is determined by the limit loss proportion method given, and further the actual number of the theoretical plates and the height are calculated by using the redundancy coefficient found to complete the whole design as shown in the computational sample. Research show that the actual number of the theoretical plates and the height of batch distillation column with the column diameter 0.6 m are 17 and 5.1 m in an alcohol mixture separation system of the example provided. Moreover, the approach can be extended to the design of batch distillation column with a separation system of multi-component liquid mixture after those adjacent components are treated as numerous binary component systems. Finally, recent trends with regarding to extension and application of separation difficulty in investigation areas of separation engineering are expounded based on the concept given, and potential hot spots such as the relations between the entropy value and the separation difficulty for a hybrid system are predicted.